Blockchain-based smart contract for international business – a framework. (26th February 2021) - Sinha, Deepankar; Roy Chowdhury, Shuvo
Abstract : Purpose: Cross border trade, involving different business environments between the sellers' and buyers' countries, may result in conflicts because of asymmetry in the information structure across the borders. The International Chambers of Commerce (ICC) has laid down ground rules on terms of shipment and payment, enabling harmonization and standardization of business process, and fixing of responsibilities for international trade. The international commercial (INCO) terms by ICC define the duties, obligations and cost borne by the exporter and the importer. An exporter's uncertainty looms once the goods cross his/her border. Therefore, there is a need for a smart contract that is secured, transparent, legitimate and trustworthy. The authors propose a blockchain technology-based smart global contract (BTGC) framework for international trade. Design/methodology/approach: In this paper, the authors develop the framework based on value chain analysis (VCA) of international trade and an ontology-driven-blockchain-design approach. The paper analyzes the sequence of activities in the value chain of global trade, the terms of the contract, the data structure templates, the validation rules and the points-of-failure, and proposes the smart contract blockchain structure. Findings: This paper proposes the BTGC framework considering the INCO terms 2020; it provides the validation rules and the probability of failures; and identifies the elements that cause the halting of contracts and conditions of creation of side blockchains. The framework also includes the governance of the BTGC system. Research limitations/implications: The proposed framework not only has implications at the firm level as it automates and secures a global sale contract but also is expected to harmonize the global-trade process as well. The developers may use the attributes, data structure templates and the rules identified in this paper for developing the GC software. Future research may consider using case analysis, class diagrams and the related steps for developing the blockchain software. Originality/value: This paper proposes a complete value chain of global contract (GC) concerning exports, an ontology of GC and a blockchain-based smart-contract framework based on global standards. Besides, it specifies the elements of fraud (such as the non-integration of side chains) and uncertainty, i.e. the probability of failures. Such a framework will harmonize the global-trade process and build an international standards for smart GC based on blockchain technology (ISSGCBT), which is not yet done.